2020
DOI: 10.1073/pnas.1915888117
|View full text |Cite|
|
Sign up to set email alerts
|

High-resolution structural insights into the heliorhodopsin family

Abstract: Rhodopsins are the most abundant light-harvesting proteins. A new family of rhodopsins, heliorhodopsins (HeRs), has recently been discovered. Unlike in the known rhodopsins, in HeRs the N termini face the cytoplasm. The function of HeRs remains unknown. We present the structures of the bacterial HeR-48C12 in two states at the resolution of 1.5 Å, which highlight its remarkable difference from all known rhodopsins. The interior of HeR’s extracellular part is completely hydrophobic, while the cytoplasmic part co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
162
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(178 citation statements)
references
References 75 publications
8
162
1
Order By: Relevance
“…The vibrational coupling of the ν(C=C) and δ(N-H) modes indicates different Schiff base geometry in HeRs and other known microbial rhodopsins. These results agree with structural data, which demonstrated distinct retinal pocket organization of HeRs [296]. Nevertheless, Figure 13 shows that the RR spectra of heliorhodopsin HeR 48C12 have a lot of similarities with other microbial rhodopsin spectra although the protein has unique structural features and unclear function.…”
Section: Rs Of Microbial Rhodopsinssupporting
confidence: 85%
See 1 more Smart Citation
“…The vibrational coupling of the ν(C=C) and δ(N-H) modes indicates different Schiff base geometry in HeRs and other known microbial rhodopsins. These results agree with structural data, which demonstrated distinct retinal pocket organization of HeRs [296]. Nevertheless, Figure 13 shows that the RR spectra of heliorhodopsin HeR 48C12 have a lot of similarities with other microbial rhodopsin spectra although the protein has unique structural features and unclear function.…”
Section: Rs Of Microbial Rhodopsinssupporting
confidence: 85%
“…At this moment, the conception of optogenetics covers a lot of applications, i.e., fundamental study of inner membrane structures of the cell, peripheral nervous system investigation, degenerative retina prosthetics, and a lot more. Robust development in this field opened new era of microbial rhodopsins study [292,293] and generated a tsunami of structural-functional studies of retinal proteins that aimed at the development of new optogenetic tools [19,[293][294][295][296][297][298][299][300]. Advanced RS, such as resonance, time-resolved, SRS provide exclusive information regarding their functional and structural peculiarities, thus facilitating the design of novel optogenetic tools.…”
Section: Rs Of Microbial Rhodopsinsmentioning
confidence: 99%
“…Recently, a distinct and abundant group of microbial rhodopsins, HeRs, has been discovered 37 39 . Although HeRs share low sequence identity with the other rhodopsins and adopt the inverted membrane topology, the crystal structures revealed that HeR comprises seven TMs with the retinal chromophore, as in the other rhodopsins 40 42 . Unlike these rhodopsins, the enzyme rhodopsins have long N-termini, and are predicted to have 1–2 additional transmembrane helices 11 , 12 , 43 , while the existence of TM0 and its function still have remained to be elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…TMs with the retinal chromophore, as in the other rhodopsins [39][40][41] . Unlike these rhodopsins, the enzyme rhodopsins have long N-termini, and are predicted to have 1-2 additional transmembrane helices 11,12,42 , while the existence of TM0 and its function still have remained to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a distinct and abundant group of microbial rhodopsins, the heliorhodopsins (HeRs) has been discovered [36][37][38] . Although HeRs share low sequence identity with the other rhodopsins and adopt the inverted membrane topology, the crystal structures revealed that HeR comprises 7TMs with the retinal chromophore, as in the other rhodopsins [39][40][41] . Unlike these rhodopsins, the enzyme rhodopsins have long N-termini, and are predicted to have 1-2 additional transmembrane helices 11,12,42 , while the existence of TM0 and its function still have remained to be elucidated.…”
mentioning
confidence: 94%